Systematic Literature Review: Analysis Of The Influence Of Transformational Leadership Style And Work Motivation On Teacher Performance - Enita, Fery; Wening, Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
The teacher is one of the elements that drives the Teaching and Learning Activities (KBM) process. It can be said that teachers are the main actors in education who will influence the quality of student achievement. Therefore, to analyze this, the researcher included variable teacher performance as a factor in the implementation of learning objectives. This research is a qualitative type with a Systematic Literature Review (SLR) approach by taking 10 scientific articles for analysis. This research aims to present the variables transformational leadership style (X1), work motivation (X2), and teacher performance (Y). From the conclusions of these 10 articles, the researcher concluded that the principal's transformational leadership is very important for teacher performance because it relates to how a school principal conveys the vision, mission, goals, regulations and programs set by the school so that teachers can plan and have targets to develop themselves as a whole. Creative and innovative, such as increasing functional positions and increasing knowledge. The work motivation variable also has a direct effect on teacher performance. This means that changes in increasing work motivation will lead to increased teacher performance. Work motivation also encourages teacher growth and empowerment. Thus, the variables of transformational leadership and work motivation must be increased and improved so that teacher performance can provide optimal influence and contribution to the development and progress of education in Indonesia.